MOTIVASI DAN PERAN LINGKUNGAN TERHADAP MINAT BERWIRAUSAHA DI KALANGAN REMAJA (STUDI KASUS REMAJA DESA PASIRANGIN CILEUNGSI BOGOR) - Sri Sungkowati; Rozikin Rozikin (Jurnal Manajemen FE-UB, 2019)
This research is motivated by low interest in entrepreneurship among adolescents. Teenagersare still oriented after graduation they are more interested in working in factories, companies orgovernment agencies.The purpose of this study was to study motivation, the role of the environment (internal andexternal) towards entrepreneurial interest among youth in Desa Pasirangin Cileungsi Bogor.The method used in this research is descriptive verification by discussing ex post facto andsurveys. Data collected through questionnaires and interviews. Hypothesis testing uses simplelinear regression formula and multiple linear regression formula.Based on the analysis of the data obtained the following results: (1) Positive and significantinfluence between entrepreneurial motivation on entrepreneurial interest (2) Positive andsignificant influence of the internal environment on entrepreneurial interest (3) 4) Has positive andsignificant influence between entrepreneurial motivation, internal environment, and externalenvironment together towards the interests of youth entrepreneurship in Desa Pasirangin.keywords : entrepreneurship interest, internal environment, external environment, andentrepreneurship motivation